Trust management in social Internet of vehicles: Factors, challenges, blockchain, and fog solutions. (January 2019) - Iqbal, Razi; Butt, Talal Ashraf; Afzaal, Muhammad; Salah, Khaled
The Internet of things is the next stage in the evolution of the Internet that is being materialized with the integration of billions of smart objects. The state-of-the-art communication technologies have enabled the previously isolated devices to become an active part of the Internet. This constant connectivity opens new avenues for novel applications such as the realization of social Internet of things and its subdomain the social Internet of vehicles. Socializing requires sharing of information that entails trust, especially in an open and broad social environment. This article highlights the key factors involved in conceptualizing an efficient trust model for social Internet of vehicles. Furthermore, it focuses on the unique challenges involved in designing the trust models for social Internet of vehicles. Several trust models exist in literature; however, most of the existing trust models are specific to their domains, for example, Internet of things, social Internet of things, or general vehicular networks. This article presents a brief review of the trust models that have the potential to be implemented in Social Internet of vehicles. Finally, the authors present an overview of how trending concepts and emerging technologies like blockchain and fog computing can assist in developing a trust-based social Internet of vehicles model for high-efficiency, decentralized architecture and dynamic nature of vehicular networks.